The magnolia duchess [large type] : a novel - White, Beth, 1957- (White, Beth, 1957- Gulf Coast chronicles ;, 2016)
Fiona Lanier is the only woman in the tiny Gulf Coast settlement of Navy Cove. While her shipbuilding family races to fill the demand for American ships brought by the War of 1812, Fiona tries to rescue her brother who was forced into service by the British Navy. Lieutenant Charlie Kincaid has been undercover for six months, obtaining information vital to the planned British invasion of New Orleans. When a summer storm south of Mobile Bay wrecks his ship and scatters the crew, Charlie suffers a head injury, ultimately collapsing in the arms of a beautiful mermaid who seems eerily familiar. As Charlie's memory returns in agonizing jags and crashes, he and Fiona discover that falling in love may be as inevitable as the tide. But when political loyalties begin to collide, they'll each have to decide where their true heart lies.